Ethanolic extract of pomegranate (Punica granatum L) peel: acute toxicity tests on zebrafish (Danio rerio) embryos and its toxicity prediction by in silico - Indra Wibowo, Kurnia Permadi, Rika Hartati, Sophi Damayanti (Journal of Applied Pharmaceutical Science, 2018)
Antibiotic resistance causes many serious health problems that have emerged both in developed and developing countries. One of many examples of the antibiotic problem is resistance to Mycobacterium tuberculosis in tuberculosis standard therapy. Various treatments have been done to overcome Mycobacterium tuberculosis resistance. Therefore, developing new compound or supplement from a natural product is widely explored. Pomegranate fruit (Punica granatum L) has been used traditionally as an antimicrobial agent. However, its toxicity should be investigated prior to development. This research was aimed to determine LC50 of the ethanolic extract and to predict the toxicity of the compound in vivo and in silico, respectively. The fish embryo acute toxicity test was done by using zebrafish (Danio rerio) embryos as subject to obtained safety characteristics of extract. Toxicities of compounds in pomegranate were predicted using software ADMET Predictor 7.1. Pomegranate peel ethanol extract revealed LC50 of 196,037 ± 9,2 μg/mL. Based on OECD aquatic toxicity classification, pomegranate peel ethanol extract was classified as safe. Toxicity prediction showed that brevifolin was the safest substance among the other substances that are contained in ethanol extract of pomegranate peel. Further research based on this result may lead to improving further natural drug development to overcome the resistance of antibiotic in tuberculosis.
Keywords: Pomegranate peel, zebrafish,toxicity test, in vivo, insilico, molecular.